Choosing between gifts and bequests how taxes affect the timing of wealth transfers - Joulfaian, David (National Bureau of Economic Research, 2005)
"A number of theories have been advanced to explain the size and timing of intergenerational transfers. One factor only recently explored is the effects of taxes, and in particular the estate tax, on such transfers. This paper represents the first attempt to explore how capital gains and gift taxes, in addition to the estate tax, interact to influence incentives in the timing of transfers. Using estate tax data and exploiting variations in state inheritance, gift, and capital gains tax rates, this paper finds taxes to be an important consideration in the choice between gifts and bequests. In particular, each of capital gains and gift taxes are found to be important determinants of the timing of transfers. These findings are robust to a number of specifications that control for borrowing, charitable bequests, marital status, and the portfolio composition of wealth transfers"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Inheritance and succession -- Econometric models; Inheritance and transfer tax